Dysgerminoma of the Ovary: An Analysis of 140 Cases Emphasizing Unusual Microscopic Findings and Resultant Diagnostic Problems. (August 2021) - Warnnissorn, Malee; Watkins, Jaclyn C.; Young, Robert H.
Abstract : One-hundred fourty pure dysgerminomas were evaluated with particular focus on the microscopic features as seen in 125 cases with available slides. The patients ranged from 8 to 59 years of age (mean, 24.1 y). The tumors, bilateral in 4% of the cases and with a mean tumor diameter of 13 cm, were typically soft, lobulated, homogeneous, and creamy white to tan to yellow but necrosis was found in 13%, hemorrhage in 20%, and focal cystic change in 15%. On microscopic examination, the patterns and other notable features encountered, including their frequency, were as follows: an alveolar pattern resulting from delicate fibrovascular septa (51%), diffuse (33%), macronodular (14%), insular (26%), cords (28%), solid tubular (17%), microspaces (sometimes simulating glands) (12%), follicle-like spaces (5%), prominent fibrous bands (65%), stromal edema (56%), stromal luteinization (9%), granulomatous infiltrate (46%), lymphocytic infiltrate (100%), Langhans cell type giant cells (35%), syncytiotrophoblast giant cells (6%), prominent population of cells with pale to clear cytoplasm (73%), cells with amphophilic to eosinophilic cytoplasm (53%) and vacuolated occasionally signet ring-like cells (7%). Various constellations of the above findings often resulted in an appearance different from that usually portrayed in the literature and certain tumors of very different nature being in the differential such as undifferentiated carcinoma not otherwise specified, small cell carcinoma of hypercalcemic type, and malignant lymphoma. The correct diagnosis can be arrived at by considering the usual relative youth of the patient, often rather characteristic gross features, and most crucially careful attention to the microscopic features and awareness of variant morphologic findings. Those that are particularly problematic based on this study are diffuse growth with inconspicuous fibrovascular septa, macronodules, cords, solid tubular formations, spaces ranging from small to large, and mimicking glands or follicles, prominent fibrous to edematous stroma, and cells with amphophilic to eosinophilic cytoplasm. According to the degree of difficulty and confidence of the interpreter, well-known immunohistochemical features of dysgerminoma, which largely differ from those of other neoplasms in the differential, will aid if felt indicated.